Penerapan Model Pembelajaran Inkuiri dalam Meningkatkan Kemampuan Komunikasi Anak Usia 5-6 Tahun di TK Aisyiyah Bustanul Athfal IV - Dea Angriani Pautina; Annisa Fahmi Mannassai; Hestia Karim; Meldasari Taeli; Sartika Panantu (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
This study aims to determine the application of the inquiry learning model in improving the communication skills of children aged 5-6 years in Aisyiyah Bustanul Athfal IV Kindergarten. This study uses a qualitative approach with data collection techniques in the form of observation and in-depth interviews. The research subjects consisted of 15 children in class B2. The focus of the research is directed at children's communication skills which include the courage to speak, the ability to ask questions, express opinions, and interact with peers and teachers during the learning process. The results of the study show that the application of the inquiry learning model is able to create an active, participatory, and child-centered learning atmosphere so as to encourage a significant improvement in communication skills. Children become more confident in conveying ideas and engaging in simple discussions. Although there are some obstacles, such as children's overactive behavior and differences in parents' views on the curriculum, these obstacles can be overcome through a personal approach and good cooperation between teachers and parents. Thus, the inquiry learning model is considered effective in improving early childhood communication skills.